FERROMAGNETIC CORE-SHELL COAXIAL NANOSTRUCTURES ON GALLIUM ARSENIDE SUBSTRATES - Monaico, E. V.; Morari, V.; Kutuzau, M.; Ursaki, V. V.; Nielsch, Kornelius; Tiginyanu, I. M. (Romanian Journal of Physics, 2022)
Fe and NiFe coatings have been electrochemically deposited on GaAs nanowires arrays prepared by electrochemical etching of (001) and (111)B GaAs substrates in a 1M HNO3 electrolyte. It was found that deposition in galvanostatic mode is preferable for Fe coatings, while it is not suitable for NiFe alloys. Potentiostatic deposition was applied for Ni0.65Fe0.35 coatings. The fabricated ferromagnetic coaxial core-shell structures have been investigated by means of scanning electron microscopy (SEM) and vibrating sample magnetometry (VSM). A comparative analysis of magnetic properties of the produced structures in terms of saturation and remanence moment, squareness ratio, and coercivity, was performed between planar and coaxial structures, between Fe and NiFe coatings, as well as between different orientations of the magnetic field with respect to the nanowires axis.
CRIS-Team Scopus Importer:2023-03-20
Keywords: anodization; core-shell structures; electroplating; hysteresis loop; magnetic anisotropy; magnetic properties of interfaces; nanotubes; Nanowires